Disasters and Economic Welfare : Can National Savings Help Explain Post-disaster Changes in Consumption? - Mechler, Reinhard (2012)
The debate on whether natural disasters cause significant macroeconomic impacts and indeed hinder development is ongoing. Most analyses along these lines have focused on impacts on gross domestic product. This paper looks beyond this standard national accounting aggregate, and examines whether traditional and alternative national savings measures combined with adjustments for the destruction of capital stocks may contribute to better explaining post-disaster changes in welfare as measured by changes in consumption expenditure. The author concludes that including disaster asset losses may help to better explain variations in post-disaster consumption, albeit almost exclusively for the group of low-income countries. The observed effect is rather small and in the range of a few percent of the explained variation. For low-income countries, capital stock and changes therein, such as forced by disaster shocks, seem to play a more important role than for higher-income economies, where human capital and technological progress become crucial. There are important data constraints and uncertainties, particularly regarding the quality of disaster loss data and the shares of capital stock losses therein. Another important challenge potentially biasing the results is the lack of data on alternative savings measures for many disaster-exposed lower-income countries and small island states.